A Distributional Record of Bolbitis Subcrenatoides Fras. -Jenk. From Matheran, Western Ghats, Sahyadri Hills, Maharashtra, India (International Journal of Scientific Research in Science and Technology, 2025)
The authors are involved in the revision of fern of the Sahyadri hills in weastern ghats of Maharashtra state, India. Through studies on ferns of the weastern ghats Maharashtra. Now survey of a fern species was carried out in Matheran forest. The present paper deals with the extended and distributional record of Bolbitis genus. A Bolbitis species it was already recorded in Amboli, weastern ghats Maharashtra. During this study tour they came across a fern with dimorphic fronds which turned, now it is collected from this 'Forest on Top area. It was calm from this region and known as Bolbitis Subcrenatoides Fras. -Jenk.
Keywords: Dimorphic fern; Matheran; Sahyadri hills; Western Ghats